Features of the System Approach at Studydefense-Industrial Complex of Ukraine - I B Chepkov; M I Lukhanin; V. Ye. Sirenko; M. A. Chernega (Mechanics and Advanced Technologies)
The article considers one of the possible approaches to the analysis of the military-industrial complex of Ukraine from the point of view of a systematic approach.